Nanomaterials : the original product of nanotechnology - Maria Benelmekki (IOP Concise Physics,, 2019)
Nanomaterials and nanostructures are the original product of nanotechnology, and the key building blocks for enabling technologies. In this context, this book presents a concise overview of the synthesis and characterization methods of nanomaterials and nanostructures, while integrating facets of physics, chemistry, and engineering. The book summarizes the fundamentals and technical approaches in synthesis, and processing of nanostructures and nanomaterials, giving the reader a systematic and quick picture of the field.- Resumé vydavatel